A resonant ionization spectroscopy scheme for photodetachment studies. Issue 13 (January 2020) - Welander, J; Navarrete, J E Navarro; Kodambattil, M; Sundberg, J; Lu, D; Hanstorp, D
Synopsis: A refined Resonant Ionization Spectroscopy (RIS) scheme for high resolution Laser Photodetachment Threshold Spectroscopy (LPTS). In this work the scheme is used to measure the electron affinity of cesium.